Egg Consumption Level and The Variation of Production-Consumption Balancing Among Provinces in Indonesia - A Rozany Nurmanaf (Indonesian Center for Animal Research and Development, 2003)
The egg is one of animal protein sources which content good nutrition for human life. Egg consumption is larger than the consumption of another animal production because it was easy to found and cheaper in price. Aggregate egg production increase significantly, especially in the years after 1980 and it continued consistently until now. The higher or the lower of egg production are affected by several development supporting factors. Egg production produced by commercial chicken farming system have a larger production contribution and become larger and larger from time to time, but in the same time the egg production contribution from native chicken and duck are precisely decrease. That is because egg production rate of those two are slower. Consumption rate variation is close relation with the specific tradition of the region, like local culture, tradition and habit of community. These features affect consumption pattern of the society. Production-consumption balancing vary among provinces. Balanced ratio of those, production and consumption, yields three criteria, namely the provinces which have surplus balancing, sufficien balancing and deficit balancing. The provinces with surplus balancing can be called as the egg supplier for other provinces with deficit balancing. Key words: Egg production, egg consumption, production-consumption path